Detección molecular del virus de Lengua Azul en Culicoides insignis y en ovinos de Pucallpa, Perú - Navarro M., Dennis (2019)
The aim of the present study was to detect the RNA of the Bluetongue virus (BTV) in Culicoides insignis and in blood samples of sheep reared under an extensive production system in Pucallpa, Peru. In a first phase, sheep blodd samples (n=46) were obtained from three farms to detect serum antibodies against BTV by agar gel immunodiffusion (AGID) and a competitive ELISA. Results showed that 46.7, 81.3 and 20.0% of sheep had antibodies by IDGA, of which 96% were positive to antibodies against VTV by the ELISA test. In the second phase, 1143 Culicoides spp were captured and 15 sheep blood samples were collected in the seropositive farms. One thousand females of Culicoides insignis were identified. The females were grouped into pools of 100 each (C. insignis = 10 pools and Culicoides spp = 1). For the molecular analysis, the extraction of total RNA was carried out from the ovine blood samples and Culicoides, followed by a nested PCR using two pairs of specific primers that amplified seg 7 of BTV. Only one pool of C. insignis and one sheep blood sample showed a band of approximately 1070 bp. The presence of viral RNA in the pool of C. insignis and in the ovine suggest the possible role of C. insignis as a potential vector for the transmission of BTV in sheep of the farms under study.